Сучасний урок в музеях художньо-мистецького профілю України і Польщі - Василишин, Марія (Studies in Comparative Education, 2015)
У статті проаналізовано особливості організації та проведення уроків у музеях художньо-мистецького профілю України і Польщі. Визначено основні типи музейних уроків, методи та прийоми активізації пізнавальної діяль-ності учнів у середовищі музею. Обґрунтовано значення музейних уроків для розкриття творчого потенціалу учнів. Проанализированы особенности организации и проведения музейных уроков в музеях художественно-творческого профиля Украины и Польши. Определены основные типы музейных уроков, методы и приемы активизации познавательной деятельности учащихся в среде музея. Обосновано значение музейных уроков для раскрытия творческого потенциала учащихся. The peculiarities of museum lessons’ organization and realization in the art and artistic museums of Ukraine and Poland are analyzed. It is said that museum lesson is a lesson at the museum or the museum exhibition using interactive technologies for different age categories of students. Museum lesson is organized by students in order to gain knowledge of a particular curriculum or to consolidate and deepen the skills acquired in the ordinary classroom. Realization of lessons in the museum involves the creation of a special educational environment that contributes to acquiring knowledge by students and application them in educational activities. The term “museum environment” is presented as a set of museum objects that are used in the museum and educational cooperation. The main types of museum lessons are characterized. Among them are excursions, lectures, tours, discussions, travels and meetings with prominent figures, museum and educational festivals, birthday parties in the museum. These specialized forms of museum activity have the aim to inform children as well as to form their skills and contribute to the formation of their artistic culture. Some methods and techniques of improving the cognitive activity of students in the museum environment in Ukraine and Poland are determined. The differences can be seen in various approaches to the organization of museum interaction. In particular, the museum lessons in Ukraine provide mainly focus on academic, formal education, which implements educational objectives of a specific subject curriculum at museums. They develop knowledge firmly fixed in the memory. At the same time the museum lessons and workshops take place in Poland within the formal education and have considerable creative and developmental potential, stimulate students to scientific research and actually implement the principle of “lifelong learning”. Also, the role of museum lessons in the development of creational potential of students is proved and explained. Using interactive methods of learning activities in the museum classrooms in Ukraine and Poland promotes cognitive interests of pupils, their life competences. Skilful combination of traditional and interactive methods of learning activities provides high efficiency of museum lessons, children’s wish to learn new and interesting information and appropriate level of academic performance of students.